Вычислите:

(a^2+4a)^2-a^2(a-2)(a+2)-4a^2(2a-1)=

(x-4)^2-(x+1)(x+2)=

16-(y+1)^2=

-3a^2-6ab-3b^2=

b(b-2)^2+b^2(2-b)=

1

Ответы и объяснения

2013-02-07T11:38:31+00:00

1) = a^4 - 8a^3 + 16a^2 - a^2(a^2-4) - 4a^2(2a-1) = a^4 - 8a^3 + 16a^2 - a^4 + 4a^2 - 8a^3 + 4a^2 = -16a^3 + 24a^2 = 8a^2 (3 - 2a)

2) = x^2 - 8x + 16 - (x^2+2x+x+2) = x^2 - 8x + 16 - x^2 - 3x - 2 = 14 - 11x

3) = 16 - (y^2 - 2y +1) = 16 - y^2 + 2y - 1 = -y^2 + 2y +15

4) -3(a^2+2ab+b^2) = -3(a+b)^2

5) = b(b^2-4b+4)+ 2b^2-b^3 = b^3 - 4b^2 + 4b + 2b^2 - b^3 = -2b^2 + 4b = 2b(2-b)